Development of the Ajinomoto Group Nutrient Profiling System for Japanese Meals - Jinzu, Hiroko; Arima, Keishiro; Kobayashi, Hiroaki; Sakai, Shunji; Nii, Sachi; Nakayama, Yuki; Okabe, Yuki; Furuta, Chie (Frontiers in Nutrition, 2025)
IntroductionNutrient profiling (NP) is a method used to classify or score foods based on their nutritional content and impact on human health. The Ajinomoto Group Nutrient Profiling System (ANPS) was previously developed to evaluate the nutritional value of cooked dishes consumed in Japan. This study aimed to develop a novel NP model, named the Ajinomoto Group Nutrient Profiling System for Japanese Meals (ANPS-Meal), to evaluate meals.MethodsThe ANPS-Meal evaluates meals using essential components based on public health concerns specific to Japan. The scoring algorithm includes protein and vegetables for encouraged intake and saturated fatty acids and sodium for limited intake. The convergent validity of this model was verified by comparison with the metric Healthy Eating Index-2015 (mHEI-2015) and the Nutrient-Rich Food Index 9.3 (NRF9.3).ResultsA total of 1,816 meals commonly consumed in Japan were evaluated using the ANPS-Meal. The average ANPS-Meal score was 73.7 (standard deviation = 15.5), with a median of 75 (interquartile range = 62.5–85) and a range of 27.5–100. High-scoring meals featured low sodium and high vegetables. The higher quartiles of the ANPS-Meal were associated with higher carbohydrate, dietary fiber, potassium, calcium, magnesium, iron, and vitamins A, D, and C, as well as lower fat content. Spearman’s correlation coefficients were r = 0.59 for the mHEI-2015 and r = 0.40 for the NRF9.3.DiscussionThe newly developed ANPS-Meal can be used for evaluating the overall nutritional value of a wide variety of meals based on four components: protein, vegetables, saturated fatty acids, and sodium. This model provides a comprehensive tool for assessing meal quality in alignment with public health objectives specific to Japan.